Preparation method and application of Fe-Mn doped phenolic resin-based carbon material

The PMS is activated by Fe-Mn-doped phenolic resin-based carbon material, and the problem of complex preparation process of phenolic resin carbon material in the prior art is solved, and the effect of efficiently and stably removing dyes in water is achieved.

CN119488919APending Publication Date: 2025-02-21GUANGXI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411613775.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing phenolic resin carbon materials have complex preparation processes, serious environmental pollution, and it is difficult to efficiently remove water neutral/cationic dyes.

Method used

Fe-Mn-doped phenolic resin-based carbon material is prepared by preparing alkaline aqueous solutions, hydrothermal reaction, grinding and calcining, etc., and is used to activate PMS to degrade dyes in water.

Benefits of technology

It has achieved efficient removal of water neutral/cationic dyes, high dye removal rate, TOC removal rate can reach 71%, and the material has high stability and wide applicable pH range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005131598300000041
    Figure BDA0005131598300000041
  • Figure BDA0005131598300000051
    Figure BDA0005131598300000051
  • Figure BDA0005131598300000052
    Figure BDA0005131598300000052
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a Fe-Mn doped phenolic resin-based carbon material, and belongs to the technical field of environment. The problems that a phenolic resin carbon material is complex in preparation process and seriously pollutes the environment are solved. The preparation process comprises the following steps: 1, dissolving tannic acid in an alkaline aqueous solution, then adding a formaldehyde solution, and fully stirring for reaction to obtain a tannic acid-formaldehyde oligomer solution; 2, adding ferric salt and manganese salt into the solution, fully stirring and then carrying out hydrothermal reaction to obtain a Fe-Mn doped phenolic resin composite material, washing, centrifuging, drying and grinding the Fe-Mn doped phenolic resin composite material; 3, the composite material is placed in a muffle furnace to be calcined, the Fe-Mn doped phenolic resin-based carbon material is obtained, the obtained material can be used for activating PMS to efficiently degrade anionic / cationic dye in water, the dye mineralization rate can reach 71%, and the material can be repeatedly used. The material prepared by the method is simple in preparation process, the used material is environment-friendly, and reaction conditions are easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of environmental technology, and in particular to a preparation method of a Fe-Mn-doped phenolic resin-based carbon material and application of the material in activating PMS to degrade anionic / cationic dyes in water. Background Art

[0002] In recent years, the advanced oxidation technology based on permonosulfate (PMS) has attracted widespread attention due to its advantages such as simple operation and environmental friendliness. This technology can generate highly oxidative reactive oxygen radicals (ROS) under mild conditions. These free radicals have extremely strong reactivity and can effectively degrade organic pollutants with complex structures and difficult to biodegrade, such as dyes, drug residues and toxic compounds in industrial wastewater. In the PMS activation system, the heterogeneous catalytic system has become one of the current research hotspots due to its advantages such as mild reaction conditions, low energy consumption, simple operation, recyclability and strong tolerance. This type of catalytic system can effectively improve the utilization rate of the catalyst and reduce the secondary pollution that may be generated during the reaction process. In the heterogeneous catalytic system, the development and preparation of efficient and environmentally friendly catalysts are crucial to improving treatment efficiency and reducing environmental impact.

[0003] Phenolic resin materials have important applications as catalysts or catalyst carriers in many chemical reactions, mainly because of their highly controllable pore structure, excellent chemical stability and good electrical conductivity. The carbonized phenolic resin carbon material can be optimized by adjusting the preparation process to optimize its pore structure and surface chemical properties, thereby achieving customized catalytic performance. For example, Wei et al. [Wei J, et al.Sol–gel synthesis of metal–phenolic coordination spheres and their derived carbon composites] used the sol-gel method to synthesize metal tannic acid coordination colloidal spheres. During the preparation process, tannic acid was pre-crosslinked with formaldehyde in an alkaline ethanol solution to form oligomers, and then polyphenol oligomers were cross-linked and polymerized by metal ligands to grow into coordination colloidal spheres. The regular metal-doped carbon spheres obtained after carbonization were used as sensors for nucleic acid variant analysis with single nucleotide discrimination and multifunctional precursors of electrode materials with high electrocatalytic performance. Wang et al. [Wan L, et al. Polymerization-induced colloid assembly route to iron oxide-based mesoporous microspheres for gas sensing and fenton catalysis] established a method for synthesizing mesoporous α-Fe2O3 crystalline microspheres by controlling the degree of polymerization of phenolic resin by polymerization-induced Fe(OH)3 colloid assembly method, and obtained α-Fe2O3 / C hybrid microspheres by subsequent calcination treatment, which can degrade the pollutant methylene blue (MB) through Fenton-like catalytic reaction, and has the advantages of fast degradation rate, high degradation rate, stable cycle performance, etc. The patent with publication number CN115651143A discloses a phenolic resin microsphere, porous carbon material microsphere and its preparation method and application, phenolic compound, water, aldehyde compound, alkaline catalyst and dispersion medium are mixed and reacted to obtain the phenolic resin microsphere, and then it is carbonized under an inert atmosphere to obtain porous carbon material microsphere. Patent publication number CN113321202 A discloses a method for preparing a phenolic resin-based hard carbon microsphere material. First, phenol monomers and aldehyde monomers are reacted to obtain liquid phenolic resin oligomers, which are then added to water to prepare a phenolic resin emulsion. Phenolic resin microspheres are obtained by spray drying, and phenolic resin-based hard carbon microspheres are prepared by pre-oxidation and high-temperature carbonization.The patent with publication number CN115722263B discloses the application of phenolic resin in photocatalytic water oxidation reaction. The phenolic resin is prepared by solvent / hydrothermal synthesis method using resorcinol, ethanol / methanol and formaldehyde and used as a catalyst for photocatalytic water oxidation reaction. The photocatalytic oxygen production system in which the phenolic resin participates has the advantages of high stability, simple operation, high repeatability and high oxygen production efficiency compared with the existing polymer photocatalytic oxygen production system. Summary of the invention

[0004] The invention provides a preparation method of a Fe-Mn doped phenolic resin-based carbon material, which solves the problem that the preparation process of the phenolic resin carbon material is complicated and causes serious environmental pollution. The prepared Fe-Mn doped phenolic resin-based carbon material is used to activate PMS to degrade anionic dyes and cationic dyes in water, and has a high dye removal rate, and a TOC removal rate of up to 71%. The Fe-Mn doped phenolic resin-based carbon material has high stability and a wide applicable pH range.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a Fe-Mn doped phenolic resin-based carbon material comprises the following steps:

[0007] (1) preparing an alkaline aqueous solution, adding tannic acid and formaldehyde in sequence and stirring to dissolve them, and fully stirring to react to obtain a tannic acid formaldehyde oligomer solution;

[0008] (2) adding ferrous sulfate heptahydrate and manganese nitrate tetrahydrate to the tannic acid formaldehyde oligomer solution obtained in step (1), stirring to allow them to react fully, to obtain a metal / tannic acid formaldehyde oligomer solution;

[0009] (3) subjecting the metal / tannic acid formaldehyde oligomer solution obtained in step (2) to a hydrothermal reaction at 160° C. for 4 h to obtain an Fe-Mn-doped phenolic resin composite material, denoted as Fe-Mn-TF, which is then washed, centrifuged, dried, ground using an agate mortar and passed through a 50-100 mesh sieve;

[0010] (4) The Fe-Mn-TF obtained in step (3) is placed in a muffle furnace and calcined to obtain a Fe-Mn-doped phenolic resin-based carbon material with a specific surface area controlled at 14 m 2 / g~45m 2 / g.

[0011] Furthermore: in step (1), the pH value of the alkaline aqueous solution is controlled at 10.2 to 10.9.

[0012] Furthermore: in step (1), the mass ratio of tannic acid to formaldehyde is 1:0.4-1:1.6, and the pH value of the reaction solution is controlled at 9-10 after adding tannic acid and formaldehyde.

[0013] Furthermore, in step (2), the mass ratio of the tannic acid to the total amount of ferrous sulfate heptahydrate and manganese nitrate tetrahydrate added is 2:1-2:4, and the mass ratio of ferrous sulfate heptahydrate to manganese nitrate tetrahydrate is 1:1.

[0014] Furthermore: in step (4), the calcination temperature is 400-800°C and the calcination time is 0.5-2h.

[0015] The Fe-Mn doped phenolic resin-based carbon material of the present invention can be used to activate permonosulfate to degrade anionic dyes and cationic dyes in water. Specifically, the Fe-Mn doped phenolic resin-based carbon material is added to water, and then permonosulfate is added to react at room temperature. Preferably, the amount of the Fe-Mn doped phenolic resin-based carbon material is 0.1 to 0.5 g / L. More preferably, the amount of the Fe-Mn doped phenolic resin-based carbon material is 0.3 g / L. Preferably, the initial pH of the water is 3 to 11.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. Using tannic acid instead of phenol and water instead of ethanol solution is simple to operate and is an environmentally friendly process route.

[0018] 2. Grind the material with an agate mortar and pass it through a 50-100 mesh screen. After calcination, the specific surface area of ​​the material can be controlled to 14m 2 / g~45m 2 / g.

[0019] 3. The yield of materials prepared by this process is relatively high. The yield of Fe-Mn-TF is 32.6% to 47.3%, and the yield of Fe-Mn-doped phenolic resin-based carbon materials is 17.4% to 24.6%.

[0020] 4. The ferrous sulfate heptahydrate and manganese nitrate tetrahydrate used in the present invention provide iron source and manganese source for the Fe-Mn-doped phenolic resin-based carbon material. The obtained Fe-Mn-doped phenolic resin-based carbon material is used to activate PMS to degrade anionic dyes and cationic dyes in wastewater. It has good degradation effect, high degree of dye mineralization, wide applicable pH range, excellent stability, and the removal rate of MB can still reach 92.23% after four cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XRD spectrum of the Fe-Mn doped phenolic resin based carbon material prepared in Examples 11, 1 and 12.

[0022] Figure 23 is a SEM image of the Fe-Mn doped phenolic resin-based carbon material prepared in Example 1.

[0023] Figure 3 The figure shows the removal effect of MB by the Fe-Mn doped phenolic resin based carbon material prepared in Example 1 with different dosages after activating PMS.

[0024] Figure 4 The figure shows the removal effect of the Fe-Mn doped phenolic resin-based carbon material prepared in Example 1 on MB with different initial pH values ​​after activation of PMS.

[0025] Figure 5 This is the recycling result of the Fe-Mn doped phenolic resin-based carbon material prepared in Example 1. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are clearly and completely described below in conjunction with the embodiments of the present invention.

[0027] Example 1

[0028] The preparation method of the Fe-Mn doped phenolic resin-based carbon material of this embodiment comprises the following steps:

[0029] (1) 50 mL of ultrapure water was added to a 100 mL sample bottle, 0.5 mL of aqueous ammonia (ammonia concentration 25-28 wt%) was added and stirred evenly to make the solution alkaline, and the pH value of the alkaline aqueous solution was 10.2. 0.2 g of tannic acid and 0.16 g of formaldehyde were added in sequence and stirred to dissolve, and the pH value of the reaction solution was controlled at 9-10. After sufficient reaction, a tannic acid formaldehyde oligomer solution was obtained.

[0030] (2) adding 0.05 g of ferrous sulfate heptahydrate and 0.05 g of manganese nitrate tetrahydrate to the tannic acid formaldehyde oligomer solution obtained in step (1), stirring to allow the mixture to react fully, to obtain a metal / tannic acid formaldehyde oligomer solution.

[0031] (3) The metal / tannic acid formaldehyde oligomer solution obtained in step (2) is subjected to a hydrothermal reaction at 160° C. for 4 h, cooled to room temperature in a water bath to obtain Fe-Mn-TF, washed with distilled water until neutral, centrifuged, and then dried in an oven at 80° C. for 12 h; the dried Fe-Mn-TF is ground using an agate mortar and passed through a 50-100 mesh sieve.

[0032] (4) The Fe-Mn-TF obtained in step (3) was placed in a muffle furnace and calcined at 600°C for 1 h to obtain a Fe-Mn-doped phenolic resin-based carbon material with a specific surface area of ​​44.76 m 2 / g.

[0033] The Fe-Mn doped phenolic resin based carbon material prepared in Example 1 was used to activate permonosulfate (PMS) to degrade anionic and cationic dyes in water:

[0034] 100 mL of cationic dye MB (20.0 mg / L) solution and anionic dye CR (80 mg / L) solution were added to a conical flask, and then 0.3 g / L of Fe-Mn doped phenolic resin-based carbon material was added, and then 0.4 mM PMS was added to the conical flask to start the reaction at room temperature 25°C. Samples were collected regularly and filtered through a 0.22 μm filter membrane, and the MB removal rate was 98.46%, the TOC removal rate of MB was 71.56%, the removal rate of CR was 91.15%, and the TOC removal rate of CR was 67.44%.

[0035] Example 2

[0036] The difference from Example 1 is that 1.0 mL of aqueous ammonia is added in step (1) to obtain an alkaline aqueous solution with a pH value of 10.5, and all other aspects are the same.

[0037] Example 3

[0038] The difference from Example 1 is that 1.5 mL of aqueous ammonia is added in step (1) to obtain an alkaline aqueous solution with a pH value of 10.7, and all other aspects are the same.

[0039] Example 4

[0040] The difference from Example 1 is that 2.0 mL of aqueous ammonia is added in step (1) to obtain an alkaline aqueous solution with a pH value of 10.9, and all other aspects are the same.

[0041] The Fe-Mn doped phenolic resin based carbon material prepared in Examples 2-4 was used to activate permonosulfate (PMS) to degrade the cationic dye MB in water in the same manner as in Example 1. The results are shown in Table 1.

[0042] Table 1: Yield of Fe-Mn-TF and removal effect of Fe-Mn doped phenolic resin based carbon materials on MB

[0043]

[0044] Example 5

[0045] The difference from Example 1 is that 0.08 g of formaldehyde is added in step (1), and all other aspects are the same.

[0046] Example 6

[0047] The difference from Example 1 is that 0.24 g of formaldehyde is added in step (1), and all other aspects are the same.

[0048] Example 7

[0049] The difference from Example 1 is that 0.32 g of formaldehyde is added in step (1), and all other aspects are the same.

[0050] The Fe-Mn doped phenolic resin based carbon material prepared in Examples 5-7 was used to activate permonosulfate (PMS) to degrade the cationic dye MB in water. The method was the same as that in Example 1. The results are shown in Table 2.

[0051] Table 2: Yield of Fe-Mn-TF and removal effect of Fe-Mn doped phenolic resin based carbon materials on MB

[0052]

[0053] Example 8

[0054] The difference from Example 1 is that 0.1 g of ferrous sulfate heptahydrate and 0.1 g of manganese nitrate tetrahydrate are added in step (2), and all other aspects are the same.

[0055] Example 9

[0056] The difference from Example 1 is that 0.15 g of ferrous sulfate heptahydrate and 0.15 g of manganese nitrate tetrahydrate are added in step (2), and all other aspects are the same.

[0057] Example 10

[0058] The difference from Example 1 is that 0.2 g of ferrous sulfate heptahydrate and 0.2 g of manganese nitrate tetrahydrate are added in step (2), and all other aspects are the same.

[0059] The Fe-Mn doped phenolic resin based carbon material prepared in Examples 8-10 was used to activate permonosulfate (PMS) to degrade the cationic dye MB in water in the same manner as in Example 1. The results are shown in Table 3.

[0060] Table 3: Yield of Fe-Mn-TF and removal effect of Fe-Mn doped phenolic resin based carbon materials on MB

[0061]

[0062] Embodiment 11

[0063] The difference from Example 1 is that step (4) is calcined in a muffle furnace at 400°C for 2h, and all other aspects are the same. The Fe-Mn doped phenolic resin-based carbon material obtained has a specific surface area of ​​22.44 m 2 / g.

[0064] Example 12

[0065] The difference from Example 1 is that step (4) is calcined in a muffle furnace at 800°C for 0.5h, and all other aspects are the same. The Fe-Mn doped phenolic resin-based carbon material obtained has a specific surface area of ​​14.08 m 2 / g.

[0066] The Fe-Mn doped phenolic resin based carbon material prepared in Examples 11-12 was used to activate permonosulfate (PMS) to degrade the cationic dye MB in water. The method was the same as that in Example 1. The results are shown in Table 4.

[0067] Table 4: Yield of Fe-Mn doped phenolic resin-based carbon materials and their removal effect on MB.

[0068]

[0069] Application experiment of Fe-Mn doped phenolic resin based carbon material activating PMS to degrade MB in water.

[0070] 1. Effect of Fe-Mn doped phenolic resin based carbon material dosage on MB degradation Figure 3 shown.

[0071] Preparation method of Fe-Mn doped phenolic resin based carbon material: same as Example 1.

[0072] 100 mL of MB (20.0 mg / L) solution was added to a conical flask, and then 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, and 0.5 g / L of Fe-Mn-doped phenolic resin-based carbon materials were added respectively. Then, 0.4 mM PMS was added to the conical flask to start the reaction at room temperature of 25 °C. The samples were collected regularly and filtered through a 0.22 μm filter membrane, and the removal rate of MB by Fe-Mn-doped phenolic resin-based carbon materials was measured using a UV-visible spectrophotometer. Figure 3 It can be seen that when the dosage of Fe-Mn doped phenolic resin-based carbon material increases from 0.1g / L to 0.3g / L, the removal rate of MB increases from 71.30% to 98.46%. When the dosage of Fe-Mn doped phenolic resin-based carbon material increases from 0.3g / L to 0.5g / L, the improvement in removal rate is no longer significant. The optimal dosage of Fe-Mn doped phenolic resin-based carbon material is based on cost and degradation effect considerations. Therefore, according to the results, the optimal dosage of Fe-Mn doped phenolic resin-based carbon material is 0.3g / L.

[0073] 2. Effect of initial pH on the degradation of MB by Fe-Mn-doped phenolic resin-based carbon materials Figure 4 shown.

[0074] Preparation method of Fe-Mn doped phenolic resin based carbon material: same as Example 1.

[0075] 100 mL of MB (20.0 mg / L) solution was added to a conical flask, and the pH of the solution was adjusted to 3, 5, 6.6 (unadjusted), 7, 9, and 11, respectively. Then, 0.3 g / L of Fe-Mn-doped phenolic resin-based carbon material was added, and then 0.4 mM PMS was added to the conical flask to start the reaction at room temperature 25 °C. The samples were collected regularly and filtered through a 0.22 μm filter membrane, and the removal rate of MB by Fe-Mn-doped phenolic resin-based carbon material was measured using a UV-visible spectrophotometer. Figure 4 It can be seen that the Fe-Mn doped phenolic resin-based carbon material still maintains a good degradation efficiency between the initial pH of 3 and 11. When the pH is 3, the removal rate of MB decreases, but the removal rate can still reach 92.57%.

[0076] Figure 5 : The recycling results of the Fe-Mn doped phenolic resin-based carbon material of Example 1.

[0077] Depend on Figure 5 It can be seen that even after 4 cycles of use, the removal efficiency of MB by Fe-Mn doped phenolic resin-based carbon material still remains at a high level of 92.23%.

Claims

1. A method for preparing a Fe-Mn doped phenolic resin-based carbon material, characterized in that: The following steps are involved: (1) preparing an alkaline aqueous solution, adding tannic acid and formaldehyde in sequence and stirring to dissolve them, and fully stirring to react to obtain a tannic acid formaldehyde oligomer solution; (2) adding ferrous sulfate heptahydrate and manganese nitrate tetrahydrate to the tannic acid formaldehyde oligomer solution obtained in step (1), stirring to allow the mixture to react fully, and obtaining a metal / tannic acid formaldehyde oligomer solution; (3) subjecting the metal / tannic acid formaldehyde oligomer solution obtained in step (2) to a hydrothermal reaction at 160° C. for 4 h to obtain an Fe-Mn-doped phenolic resin composite material, denoted as Fe-Mn-TF, which is then washed, centrifuged, dried, ground using an agate mortar and passed through a 50-100 mesh sieve; (4) The Fe-Mn-TF obtained in step (3) is placed in a muffle furnace and calcined to obtain a Fe-Mn-doped phenolic resin-based carbon material with a specific surface area controlled at 14 m 2 / g~45m 2 / g.

2. The preparation method according to claim 1, characterized in that: In step (1), the pH value of the alkaline aqueous solution is controlled at 10.2 to 10.

9.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of tannic acid to formaldehyde is 1:0.4-1:1.6, and the pH value of the reaction solution is controlled at 9-10 after adding tannic acid and formaldehyde.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the tannic acid to the total amount of ferrous sulfate heptahydrate and manganese nitrate tetrahydrate added is 2:1-2:4, and the mass ratio of ferrous sulfate heptahydrate to manganese nitrate tetrahydrate is 1:

1.

5. The preparation method according to claim 1, characterized in that: In step (4), the calcination temperature is 400-800°C and the calcination time is 0.5-2h.

6. Use of the Fe-Mn doped phenolic resin-based carbon material according to claim 1 in activating peroxymonosulfate to degrade anionic dyes and cationic dyes in water.

7. The use according to claim 6, characterized in that: The Fe-Mn doped phenolic resin based carbon material is added into water, and then peroxymonosulfate is added to react at room temperature.

8. The use according to claim 7, characterized in that: The Fe-Mn doped phenolic resin based carbon material is used in an amount of 0.1 to 0.5 g / L.

9. The use according to claim 8, characterized in that: The amount of the Fe-Mn doped phenolic resin-based carbon material used is 0.3 g / L.

10. The use according to claim 7, characterized in that: The initial pH of the water is 3-11.

Citation Information

Patent Citations

  • Preparation method of phenolic resin-based hard carbon microsphere material

    CN113321202A

  • Phenolic resin microspheres, porous carbon material microspheres as well as preparation method and application of phenolic resin microspheres and porous carbon material microspheres

    CN115651143A

  • Application of a phenolic resin in photocatalytic water oxidation reaction

    CN115722263B